2019
DOI: 10.1109/access.2019.2892564
|View full text |Cite
|
Sign up to set email alerts
|

Joint Positioning of Flying Base Stations and Association of Users: Evolutionary-Based Approach

Abstract: Time-varying requirements of users on communication push mobile operators to increase density of base stations. However, the dense deployment of conventional static base stations (SBSs) is not always economical, for example, when periods of peak load are short and infrequent. In such cases, several flying base stations (FlyBSs) mounted on unmanned aerial vehicles can be seen as a convenient substitution for the dense deployment of SBSs. This paper focuses on maximization of user satisfaction with provided data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…This is also the case in the work by Li et al [103]. Mobile edge devices have, to the best of our knowledge not been considered for edge servers, but Plachy et al [104] showed that mobile (in that particular case flying) base stations are beneficial for increasing the data rate a user can get.…”
Section: Placementmentioning
confidence: 77%
“…This is also the case in the work by Li et al [103]. Mobile edge devices have, to the best of our knowledge not been considered for edge servers, but Plachy et al [104] showed that mobile (in that particular case flying) base stations are beneficial for increasing the data rate a user can get.…”
Section: Placementmentioning
confidence: 77%
“…Our proposed solution for UAV-assisted IAB networks is significantly different compared to the studies in [13], [14], [19], [43], [48]. In particular, we consider the mutual dependence between backhaul, direct and access transmissions, inter-cell interference and the mutual dependence between the spatial configurations of UAVs and the spatial dynamics of ground user distribution, which are significantly challenging in UAV-based cellular scenarios.…”
Section: General Solution For Pmentioning
confidence: 99%
“…After adjusting (11c) and solving the URLLC power allocation in (13), the remaining power at each BS for the eMBB users is ρ j − k ∈Ku P * jk . The user association and power allocation problem for eMBB users is given as follows:…”
Section: B Ruin-based Problem Formulationmentioning
confidence: 99%